PENERAPAN RANK ONE DALAM KURIKULUM MERDEKA PADA MATA PELAJARAN IPAS SISWA KELAS X SMK ABDURRAB PEKANBARU - Safitri, Yulia; Noviyanti, Arma; Hidayati, Ira; Tasbal, Reza Ayu (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
AbstractThe 21st century is an open century that contains various challenges and opportunities that require the birth of qualified, superior and competitive individuals for the life of the nation's people. The purpose of this study was to determine the application of rank one in the independent curriculum in the science subjects of grade X students of SMK Abdurrab Pekanbaru. The method in this study is descriptive research. This research was conducted at SMK Abdurrab Pekanbaru, the population in this study was grade X students of the Department of Medical Laboratory Technology (TLM) and the Department of Pharmaceutical Technology (TF). The result of this study is that the use of rank one in learning has the advantage of allowing students to actively participate in learning, and can make students have a sense of pleasure and motivation to learn more diligently, so that it will affect their learning outcomes.Keywords: Rank One, Merdeka Curriculum, and IPAS